TINJAUAN TEOLOGIS TEHADAP PERAN GEMBALA DALAM MENGGEMBALAKAN JEMAAT BERDASARKAN 1TIMOTIUS 4:12 - Pulman Marbun (STT BIBLIKA JAKARTA, 2023)
A pastor is a pastor whose job is to lead a congregation or local church. A pastor is very important to understand his role in shepherding the congregation according to the truth of God's word. The purpose of this research is to investigate the role of the pastor in pastoring the congregation. The method used in this study is a qualitative method of literature study with text interpretation. The results of the study from the theological point of view of a pastor are someone who is ready to be an example in the midst of the congregation, an example in words and an example in behavior. Apart from being a role model, the pastor also plays a role in leading, guiding, leading on the right path, preaching the word of God as a spiritual need for God's people, caring for, visiting and also being a counselor for congregations that are facing various problems.